Natural phenolic metabolites with anti-angiogenic properties – a review from the chemical point of view - Sun, Qiu; Heilmann, Jörg; König, Burkhard (Beilstein Journal of Organic Chemistry, 2015)
Considering the many secondary natural metabolites available from plants, phenolic compounds play a particularly important role in human health as they occur in significant amounts in many fruits, vegetables and medicinal plants. In this review natural phenolic compounds of plant origin with significant anti-angiogenic properties are discussed. Thirteen representatives from eight different natural or natural-like phenolic subclasses are presented with an emphasis on their synthesis and methods to modify the parent compounds. When available, the consequence of structural variation on the pharmacological activity of the molecules is described.
Keywords: angiogenesis; natural phenolic compounds; structure–activity relationship; synthesis